3.119. Rozwiąż równanie: a) (2x – 3)(2x + 3) = (x + 5) ^ 2 – 9 b) 2x * (x – 3) – (x + 1)(x + 2) = (2x – 3) ^ 2 c) (2x – 1) ^ 2 – (4x + 1)(4x – 1) = 4x * (1 – 2x) d) (2x + 1) ^ 2 – 9 * (x – 1) ^ 2 = 4 – x e) (x – 1) ^ 2 + 2 * (x – 3) ^ 2 = 18 – 10x f) (2x + 5) ^ 2 – (2x – 5) ^ 2 = 3x ^ 2 + 41x – 4

3.119. Rozwiąż równanie: a) (2x – 3)(2x + 3) = (x + 5) ^ 2 – 9 b) 2x * (x – 3) – (x + 1)(x + 2) = (2x – 3) ^ 2 c) (2x – 1) ^ 2 – (4x + 1)(4x – 1) = 4x * (1 – 2x) d) (2x + 1) ^ 2 – 9 * (x – 1) ^ 2 = 4 – x e) (x – 1) ^ 2 + 2 * (x – 3) ^ 2 = 18 – 10x f) (2x + 5) ^ 2 – (2x – 5) ^ 2 = 3x ^ 2 + 41x – 4